Efektifitas Media Papan Huruf Terhadap Hasil Belajar Siswa Bahasa Indonesia Kelas 1 SDN Plamongansari 02 Semarang - Octina, Wibi Deta; Agustini, Ferina; Nuvitalia, Duwi; Wikyuni, Sri (Melati Institute, 2024)
This activity aims to determine how effective the use of Letter Board media is on Indonesian language learning outcomes for grade 1 students of SDN Plamongansari 02 Semarang. This study used a quantitative pre-experimental method with a one group pretest-posttest design. Data was collected through instruments in the form of pretest and posttest questions given before and after the use of Letter Board learning media. Based on the results of research and analysis in the field regarding the use of Letter Board media as a learning tool on student learning outcomes, it can be concluded that this media shows significant effectiveness. During the activities at SDN Plamongansari 02 Semarang, there were changes in students who were initially unable to do subtraction to be able to do it.